Pengaruh Kompetensi Aparat Pengelola Dana Desa, Komitmen Organisasi Pemerintah Desa, dan Partisipasi Masyarakat Terhadap Akuntabilitas Pengelolaan Dana Desa Di Kabupaten Gorontalo - Mada, Sarifudin; Kalangi, Lintje; Gamaliel, Hendrik (Universitas Sam Ratulangi, 2017)
Abstract. The accountability of village fund management has become a demand for local government. The existence of this demand results from the implementation of Law No. 6 of 2014 on the Village. The management of village funds in Gorontalo Regency is still far from the expectations. Problems emerging from the accountability of village fund management are related to the competence of village fund management officers, the commitment of village government organizations, and community participation. This research aims to know and analyze the influence of competence of village fund management officer, commitment of village government organization, and public participation to accountability of village fund management in Gorontalo Regency. This is a quantitative research study and data were collected by surveys or questionnaires. Population and sample are village fund management officers in Gorontalo Regency with 120 respondents. The hypothesis was tested by multiple linear regression analysis with SPSS application. The findings show that: (1). The competence of village fund management officers has a positive and significant impact on the accountability of village fund management; (2). The commitment of village government organizations has a positive and significant impact on the accountability of village fund management; (3). Community participation has a positive and significant impact on the accountability of village fund management. The coefficient of determination is 0.751. This shows that the influence of independent variables namely: the competence of the village fund management officer, the commitment of the village government organization, and the participation of the society, towards the dependent variable (the accountability of village fund management) explained by the equation model in this research is 75.10%. While the rest of 24. 90% is explained by other factors which are not included in this model. The implications of this study are to encourage the accountability of village fund management through the increased competence of village fund management officers, village government organizational commitment, and community participation.Keywords:Â Competence of village fund management officers, Commitment of village government organization, Community participation, accountability of village fund management.Abstrak. Akuntabilitas pengelolaan dana desa sudah menjadi sebuah tuntutan bagi pemerintah desa. Adanya tuntutan ini sebagai akibat implementasi Undang-Undang Nomor 6 Tahun 2014 tentang Desa. Pengelolaan dana desa di Kabupaten Gorontalo masih jauh dari harapan. Masalah yang timbul terkait akuntabilitas pengelolaan dana desa berkaitan dengan kompetensi aparat pengelola dana desa, komitmen organisasi pemerintah desa, dan partisipasi masyarakat. Penelitian ini bertujuan untuk mengetahui dan menganalisis pengaruh kompetensi aparat pengelola dana desa, komitmen organisasi pemerintah desa, dan partisipasi masyarakat terhadap akuntabilitas pengelolaan dana desa di Kabupaten Gorontalo. Jenis penelitian ini adalah penelitian kuantitatif metode survey. Populasi dan sampel adalah aparat pengelola dana desa di Kabupaten Gorontalo sejumlah 120 responden. Pengumpulan data menggunakan kusioner. Pengujian hipotesis menggunakan analisis regresi linier berganda dengan aplikasi SPSS. Hasil penelitian menunjukkan bahwa: (1). Kompetensi aparat pengelola dana desa berpengaruh positif dan signifikan terhadap akuntabilitas pengelolaan dana desa; (2). Komitmen organisasi pemerintah desa berpengaruh positif dan signifikan terhadap akuntabilitas pengelolaan dana desa; (3). Partisipasi masyarakat berpengaruh positif dan signifikan terhadap akuntabilitas pengelolaan dana desa. Nilai koefisien determinasi adalah 0,751. Hal ini menunjukkan bahwa besarnya pengaruh variabel independen, yaitu kompetensi aparat pengelola dana desa, komitmen organisasi pemerintah desa, dan partisipasi masyarakat terhadap variabel dependen yaitu akuntabilitas pengelolaan dana desa yang diterangkan oleh model persamaan dalam penelitian ini adalah sebesar 75,10%. Sedangkan sisanya sebesar 24,90% dijelaskan oleh faktor-faktor lain yang tidak dimasukkan dalam model ini. Implikasi temuan penelitian ini adalah untuk mendorong pengelolaan dana desa yang akuntabel melalui peningkatan kompetensi aparat pengelola dana desa, komitmen organisasi pemerintah desa, dan partisipasi masyarakat.Kata kunci: Kompetensi aparat pengelola dana desa, komitmen organisasi pemerintah desa, partisipasi masyarakat, akuntabilitas pengelolaan dana desa.